Manajemen Pimpinan Dayah dalam Meningkatkan Kinerja Guru di Dayah Darussa'adah Teupin Raya - Hadi, Abdul; Zulfadli; Yani, Muhammad; Ikhbar, Samsul (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
This study aims to analyze the role of Dayah leadership management in improving teacher performance in Dayah Darussa'adah Teupin Raya. The main focus of this study is to identify the impact of leadership on teacher performance and the obstacles faced by teachers in improving the quality of learning. The research method used is a quantitative approach with a descriptive design, which involves interview techniques with leaders and the distribution of questionnaires to 20 teachers. The results of the study show that the influence of leadership on teacher performance in Dayah Darussa'adah is quite significant. The Islamic boarding school leadership has provided direction, training, and evaluation that helps improve the quality of teaching. However, there are several obstacles that affect the effectiveness of learning, namely the low professionalism of some teachers and the limitations of facilities and infrastructure. In addition, students' motivation is also disturbed due to a lack of encouragement from their families. This research contributes to the literature on leadership management in Islamic boarding schools, especially in the context of improving teacher performance, as well as providing recommendations for teacher professionalism development and improvement.